Pengaruh Latihan Karet Terhadap Kecepatan Tendangan Sabit Pada Atlet Porprov Pencak Silat - Yulisa, Yulisa; Jalil, Rasyidah (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
This study aimed to determine whether there was an effect of rubber training on the speed of the sickle kick of the athletes of porprov pencak silat in Luwu district. The method with one group pretest and posttest designs. This study used a saturated total sampling technique where the entire population become sample namely 12 athletes. This study obtained through a pretest before being given treatment and a final test (posttest) after being given treatment. The results of this study show that there is a difference in the athlete’s test scores between the pretest and posttest. It can be seen from the value (mean) that there is an increase after using rubber training. It can be concluded that rubber training has an effect or results in an increase in the speed of the sickle kick of the athletes of the porprov pencak silat Luwu district. Based on the results of the research and discussion, it can be concluded that based on the average value of the pretest of 29.58 and the posttest result of 46.17, it shows that there is a significant effect of rubber training on the speed of the sickle kick of the porprov pencak silat athletes Luwu district.